The effect of mesenchymal stromal cell sheets on the inflammatory stage of flexor tendon healing. Issue 1 (December 2016) - Shen, Hua; Kormpakis, Ioannis; Havlioglu, Necat; Linderman, Stephen; Sakiyama-Elbert, Shelly; Erickson, Isaac; Zarembinski, Thomas; Silva, Matthew; Gelberman, Richard; Thomopoulos, Stavros
Abstract Background The clinical outcomes following intrasynovial flexor tendon repair are highly variable. Excessive inflammation is a principal factor underlying the formation of adhesions at the repair surface and affecting matrix regeneration at the repair center that limit tendon excursion and impair tendon healing. A previous in-vitro study revealed that adipose-derived mesenchymal stromal cells (ASCs) modulate tendon fibroblast response to macrophage-induced inflammation. The goal of the current study was therefore to explore the effectiveness of autologous ASCs on the inflammatory stage of intrasynovial tendon healing in vivo using a clinically relevant animal model. Methods Zone II flexor tendon transections and suture repairs were performed in a canine model. Autologous ASC sheets were delivered to the surface of repaired tendons. Seven days after repair, the effects of ASCs on tendon healing, with a focus on the inflammatory response, were evaluated using gene expression assays, immunostaining, and histological assessments. Results ASCs delivered via the cell sheet infiltrated the host tendon, including the repair surface and the space between the tendon ends, as viewed histologically by tracking GFP-expressing ASCs. Gene expression results demonstrated that ASCs promoted a regenerative/anti-inflammatory M2 macrophage phenotype and regulated tendon matrix remodeling. Specifically, there were significant increases in M2-stimulator (IL-4 ), marker (CD163 andMRC1 ), and effector (VEGF ) gene expression in ASC-sheet treated tendons compared with nontreated tendons. When examining changes in extracellular matrix expression, tendon injury caused a significant increase in scar-associatedCOL3A1 expression and reductions inCOL2A1 andACAN expression. The ASC treatment effectively counteracted these changes, returning the expression levels of these genes closer to normal. Immunostaining further confirmed that ASC treatment increased CD163+ M2 cells in the repaired tendons and suppressed cell apoptosis at the repair site. Conclusions This study provides a novel approach for delivering ASCs with outcomes indicating potential for substantial modulation of the inflammatory environment and enhancement of tendon healing after flexor tendon repair.